Hot-rolled wire rod for 1960MPa-grade stranded wire and manufacturing method of hot-rolled wire rod

By using C-Si-Mn-Cr-B composition design and rapid online molten salt isothermal treatment, a fine lamellar sorbite structure is formed, which solves the problems of high alloy cost and poor microstructure uniformity in high carbon steel strands. This achieves hot-rolled wire rods with a high strength and plasticity match, reducing the risk of wire breakage and production costs.

CN120796650AActive Publication Date: 2025-10-17JIANGSU YONGGANG GROUP CO LTD

Patent Information

Application Number
CN202511308683.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-10-17
Estimated Expiration
2045-09-15

AI Technical Summary

Technical Problem

Existing technologies for improving the strength grade of steel strands suffer from problems such as high alloy costs, poor microstructure uniformity, insufficient plasticity, and low production efficiency. In particular, in high-carbon steel, network carbides and abnormal structures are easily formed, leading to a high risk of wire breakage during the drawing process.

Method used

The high-carbon composition design of C-Si-Mn-Cr-B is adopted, combined with rapid online molten salt isothermal treatment. The phase transformation structure of the wire rod is controlled by molten salt treatment in the front and rear sections, forming a mixed structure dominated by fine lamellar sorbite, avoiding network carbides and abnormal structures, improving the strength-plasticity matching, and promoting the toughening of the structure through slow cooling on the roller table.

Benefits of technology

This technology improves the strength and plasticity matching of hot-rolled wire rods for 1960MPa grade stranded wire at a lower alloy content, reduces material costs and production energy consumption, reduces the risk of wire breakage, and meets the requirements for high load-bearing stress and long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120796650A_ABST
    Figure CN120796650A_ABST
Patent Text Reader

Abstract

The invention relates to a hot-rolled wire rod for a 1960MPa-grade stranded wire and a manufacturing method of the hot-rolled wire rod, after high-carbon components of C-Si-Mn-Cr-B are rolled and spun into a wire rod, the wire rod is subjected to rapid online molten salt isothermal treatment, and the wire rod is subjected to front-section molten salt treatment, so that the wire rod is cooled at the cooling speed of more than or equal to 32 DEG C / s and enters a sorbite phase region from an austenite state; the steel wire rod is subjected to rear-section molten salt treatment, the molten salt temperature is reduced, unconverted retained austenite is promoted to be converted into the sorbite structure, meanwhile, isothermal tempering of the structure and fusing of a part of sorbite lamellas are promoted, and finally slow cooling is conducted through a roller way; the microstructure of the hot-rolled wire rod comprises a mixed structure composed of tempered sorbite, ferrite and fused sorbite, the tensile strength is 1305-1355 MPa, the percentage reduction of area is 37%-42%, and the hot-rolled wire rod is used for being used as base metal to manufacture high-strength stranded wires and other application fields and is beneficial to reducing the risk of wire breakage.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field related to hot-rolled wire rod, and particularly relates to a 1960MPa-grade hot-rolled wire rod for stranded wire and a manufacturing method thereof. BACKGROUND

[0002] As an important load-bearing tool in high-stress environment system, steel strand is widely used in the fields of bridge, railway, building, new energy and the like. Under the development trend of lightweight, the strength grade of steel strand needs to be continuously improved. The existing improvement of the strength grade of steel strand is often through adding C and quenching elements in the hot-rolled wire rod base material to improve the strength, and even through multiple process adjustment of the microstructure and performance of the hot-rolled wire rod for stranded wire by offline quenching. However, the C and quenching elements are easy to cause abnormal microstructure such as martensite in the hot-rolled wire rod, the material plasticity is insufficient, and the alloy cost is high. The multiple offline quenching processes will cause the increase of production cost and the decrease of efficiency. Therefore, it is necessary to develop a 1960MPa-grade hot-rolled wire rod for stranded wire with uniform microstructure and matching strength and plasticity and a manufacturing method thereof, so as to control the production cost, reduce the risk of wire breakage in the subsequent drawing process, and meet the environmental requirements of higher bearing stress and longer service life.

[0003] The existing high-strength stranded wire steel hot-rolled wire rod is generally produced by combining C, quenching elements and Stelmor air cooling line. The causes of limiting the improvement of microstructure uniformity and strength and plasticity of the hot-rolled wire rod include: I. In order to improve the strength of the wire rod for wire, the prior art will increase the content of C or hardenability elements, combined with air cooling line to make wire rod with mainly sorbite structure, for example: a kind of prestressed steel strand, prestressed steel strand wire rod and its production method disclosed in patent CN112301287B, adopts C-Si-Mn-Cr-V-Al-Ti-B-Cu-Ni composition design, combined with fast and slow cooling after wire drawing on Stelmor air cooling line and high temperature coiling, the wire rod structure is mainly sorbite and a small amount of pearlite, but on the one hand, since the wire rod for wire is high carbon steel, it will aggravate the center segregation in continuous casting process, when high carbon steel austenite transforms into pearlite or sorbite, if the cooling rate is too low, carbon will have enough time to diffuse to the grain boundary and precipitate carbide, and carbide is more likely to gather on the coarse grain boundary to form continuous network, the formation of network carbide will cut off the continuity of matrix, increase the brittleness of wire rod, and cracks are easy to produce at the grain boundary during drawing, reduce the plasticity and fatigue performance of wire rod, affect the safety of steel strand in the final use, therefore, in order to reduce the level of network carbide as much as possible and promote the refinement of pearlite lamellar and improve the strength, the air cooling of wire drawing will be carried out by strong air cooling in the early stage, but due to the limitation of the maximum cooling capacity of air cooling line, the control of network carbide is limited; On the other hand, the increase of air cooling intensity also increases the temperature difference between the air cooling surface and the air cooling surface, the lap joint and the non lap joint, and the uncontrollability of air cooling amount and air temperature, with the decrease of wire rod specification, the surface is more prone to form brittle abnormal structure due to local supercooling, increase the brittleness of wire rod and the fluctuation of mechanical properties, and due to the limitation of the minimum cooling capacity of air cooling line and the slow cooling of core, the pearlite lamellar will be coarsened, and the residual austenite under high temperature coiling may lead to the formation of martensite or bainite and other hard and brittle structures in the subsequent cooling process, which reduces the overall plasticity after mixing with pearlite, and the hard and brittle area will occur plastic consumption first during drawing, and the core will not be able to bear due to insufficient strength, which will lead to rapid decline of overall plasticity and high wire breaking rate.

[0004] II. In order to control the production cost and the strength of the wire rod for stranded steel, the prior art will add V and other grain refining alloys and water cooling and other intensive cooling treatments, for example: a 1960MPa grade steel strand wire rod and preparation method, steel wire, steel strand wire rod disclosed in patent CN119082607A adopts C-Si-Mn-Cr-V composition design, combined with water mist strong cooling and air cooling to form a pearlitic structure wire rod, the strength reaches 1220MPa~1260MPa, but on the one hand, the basic performance of the steel needs to be improved by solid solution strengthening of Mn and other elements, and the initial strength of the wire rod is insufficient due to the decrease of carbon and alloy element content, the steel strand wire cold drawing strengthening needs a larger reduction rate, which leads to faster plasticity loss and higher drawing breakage rate during the process; on the other hand, a large number of bubbles will be generated during the water mist cooling process and attached to the surface of the wire rod, which will increase the cooling difference of the wire rod and make it more prone to produce brittle abnormal organization, and with the increase of the wire rod specification, the temperature difference between the surface and the core of the wire rod will further increase, which will cause the VC precipitation amount to be less or coarsen, and at the same time affect the uniformity of the phase change organization, resulting in limited strengthening effect and large organizational stress, which will further lead to the fluctuation of tensile strength and insufficient plasticity, and it is difficult to provide stable base material performance. SUMMARY

[0005] The present application aims to at least solve one of the above technical problems to some extent, and provides a 1960MPa grade stranded wire rod and a manufacturing method thereof, which can control the material cost and the uniformity of the organization, reduce the risk of network carbide level and abnormal organization, improve the high strength and plasticity matching of the wire rod, and take into account the production efficiency, provide stable stranded steel base material performance, and reduce the risk of wire breakage.

[0006] The technical scheme adopted by the present application to solve its technical problems is: A manufacturing method of a 1960MPa grade stranded wire rod, the manufacturing method comprising: The hot-rolled wire rod is produced by a wire rod production line according to the chemical composition of the hot-rolled wire rod, the chemical composition and mass percentage of the hot-rolled wire rod including: C: 0.79% to 0.83%, Si: 0.20% to 0.40%, Mn: 0.55% to 0.65%, Cr: 0.20% to 0.40%, B: 0.001% to 0.008%, P: ≤0.015%, S: ≤0.015%, and the rest being Fe and inevitable impurities; after the wire rod is drawn by a spinning machine at a spinning temperature of ≥885°C, the wire rod is subjected to rapid online molten salt isothermal treatment, the wire rod is first subjected to front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of ≥32°C / s, and enters the sorbite phase region from the austenite state, to form a structure mainly composed of sorbite structure, the wire rod is then subjected to rear-stage molten salt treatment, the molten salt temperature is reduced, the untransformed residual austenite is promoted to transform into sorbite structure, and meanwhile, the structure is promoted to perform isothermal tempering and partial sorbite lamination melting, and finally, the wire rod is subjected to slow cooling on a roller bed, to be produced into the hot-rolled wire rod with a microstructure composed of a mixed structure of tempered sorbite, ferrite and melted sorbite.

[0007] The design basis of the chemical composition and mass percentage of the hot-rolled wire rod includes: (1) Carbon: C is the main strengthening element in high-carbon steel, and the price is relatively lower. Carbon forms interstitial solid solution in the iron matrix, can improve the strength of the steel, and as an austenite stabilizing element, can lower the phase transition temperature of austenite to sorbite, so that the phase transition is carried out at a lower temperature, and then cooperate with the rapid molten salt treatment to refine the sorbite lamination spacing, provide basic strength, slow down the cementite coarsening in the isothermal tempering process, and avoid excessive loss of strength. However, if the content of C is too high, it will increase the difficulty of controlling the center segregation, network carbide and coarse carbide of high-carbon steel alloy billet, affect the toughness and cold working plasticity, therefore, in order to balance the high strength requirement of 1960MPa grade twisted wire, reduce the difficulty of controlling the uniformity of the structure, facilitate the low-temperature short-time phase transition and rapid isothermal treatment of online molten salt isothermal treatment, the content of C is appropriately reduced, and the mass percentage of C is controlled to be 0.79% to 0.83%.

[0008] (2) Silicon: Si element can be used as a deoxidizing element, and by dissolving in the iron matrix, it can produce lattice distortion and hinder dislocation movement. During the phase transition of austenite to sorbite, silicon can hinder the diffusion of carbon atoms to cementite, inhibit the growth of cementite, refine the sorbite lamination spacing and improve the tempering stability of the steel, thereby cooperating with carbon to improve the strength of the steel. However, too high silicon will promote decarburization, excessively stabilize ferrite and prolong the phase transition time, increase the difficulty of softening, and is not conducive to rapid phase transition and tempering in the online molten salt isothermal process. Therefore, in order to adapt to the regulation of the phase transition structure by rapid online molten salt isothermal treatment, the mass percentage of Si is controlled to be 0.20% to 0.40%.

[0009] (3) Manganese: Mn is an element that expands the austenite zone, can increase the recrystallization temperature of austenite, can inhibit the growth of austenite grains during rolling, and can significantly improve the hardenability of the steel, stabilize austenite through solid solution strengthening, reduce the phase change temperature of austenite to sorbite, refine the sorbite lamella, avoid the first precipitation of ferrite or coarse pearlite in the core of the wire rod, and further improve the carbon strengthening effect. However, when the content of Mn is too high, it will increase the central alloy element segregation during the solidification process of the billet, and low-temperature martensite structure is easy to form during the cooling process, which increases the risk of abnormal structure precipitation and material cost, resulting in too high hardness of the structure, and is not conducive to the promotion of sorbite rapid melting and tempering softening in the later stage of molten salt treatment, thereby reducing the plasticity of the wire rod. Therefore, in order to balance the high strength and plasticity of the hot-rolled wire rod and reduce the difficulty of controlling the uniformity of the structure, the content of Mn is appropriately reduced, and the mass percentage of Mn is controlled to be 0.55% to 0.65%.

[0010] (4) Chromium: Cr is a strong carbide-forming element, which is easy to form alloy carbides and distribute in the sorbite lamella to increase the hardness of the structure, can prolong the stability of austenite and enhance the hardenability of austenite, cooperate with online molten salt rapid cooling to inhibit the premature decomposition of austenite into ferrite or coarse pearlite during the cooling process, so that the continuous cooling transformation curve of the steel moves to the right, and fine lamellar sorbite can be easily formed at the same cooling rate, which can improve the work hardening rate of the wire rod in the subsequent drawing process. However, too high content of Cr will aggravate the segregation of alloy elements, increase the risk of abnormal structure precipitation, performance fluctuation and material cost, and reduce the activity of carbon in the steel, which is not conducive to the melting of sorbite and tempering softening, resulting in increased difficulty in improving plasticity and affecting the rapid treatment of online molten salt. Therefore, the mass percentage of Cr is controlled to be 0.20% to 0.40%.

[0011] (5) Boron: A small amount of B in steel preferentially enriches in the austenite grain boundary to form a low-energy interface layer, which can effectively improve the hardenability of the steel, reduce the excessive dependence on the content of carbon and chromium, inhibit the nucleation of austenite to pearlite / ferrite, cooperate with Mn and Cr to avoid the phase change lag or incomplete phase change of the wire rod due to insufficient hardenability, which is beneficial to the rapid treatment of online molten salt, so that the whole cross section forms a uniform structure mainly composed of sorbite. During isothermal tempering, B does not interfere with the melting and tempering softening of sorbite lamella. However, the price of B is relatively high, and excessive addition is not conducive to controlling the material cost. Meanwhile, excessive boron will form brittle boride, and hard and brittle phase will distribute along the grain boundary, which will reduce the toughness and cold working plasticity of the steel. Therefore, the mass percentage of B is controlled to be 0.001% to 0.008%.

[0012] (6) Phosphorus and sulfur: P and S elements are impurity elements, the lower the better, so P≤0.015% and S≤0.015% are controlled.

[0013] The wire rod adopts a high-carbon composition design of C-Si-Mn-Cr-B, the C or alloy content is appropriately lower than that of the existing stranded wire steel wire rod, does not contain V and other elements, and B is added in a small amount, so that the material cost can be appropriately controlled, the basic strength is improved through the cooperation of C and Si, the austenite region is expanded by cooperation with manganese, the phase transition temperature is reduced by cooperation with chromium, and the grain boundary phase transition is inhibited by cooperation with boron, so as to control the hardenability of the wire rod, the sorbite phase transition temperature interval and the resistance to temper softening, provide favorable conditions for delaying the decomposition of the austenite in the core of the wire rod, promoting the formation of uniform structure by on-line molten salt rapid short-time phase transition, reducing the interlamellar spacing of sorbite and softening difficulty, and on this basis, a higher wire laying temperature is adopted to ensure that the wire rod is in a high-temperature austenitizing state, prevent the precipitation of network carbide in advance, and the wire rod after wire laying is not subjected to Stelmor air cooling line but is subjected to rapid on-line molten salt treatment: I. Compared with the high-carbon steel wire rod in the Stelmor air cooling phase transition process, the network carbide or abnormal organization is difficult to inhibit, which weakens the strengthening effect and affects the uniformity of the organization. On the one hand, the front-stage molten salt treatment can utilize the high thermal conductivity of molten salt which is much higher than air to quickly take away the heat of the wire rod. Under high cooling rate, the austenite is rapidly cooled to the sorbite phase transition region, and the sorbite phase transition temperature is reduced by the composition design, so that the atomic diffusion coefficient is sharply reduced and the austenite grain coarsening is inhibited. The grain boundary area increases, and carbon is difficult to gather in the grain boundary to form coarse continuous network carbide, thereby avoiding the adverse effects of network carbide on strength and plasticity and the uniformity of the organization, so as to promote the formation of fine lamellar cementite which is dispersedly distributed; on the other hand, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for uniform heat exchange. Compared with air cooling, there is no temperature difference between the wind surface and the wind surface, the lap joint and the non-lap joint, and compared with water cooling, there is no problem of a large number of bubbles interfering with heat transfer. With the delay of the decomposition of the austenite in the core of the wire rod, the uniform high heat transfer can be utilized to promote the wire rod surface and the core to enter the sorbite phase transition interval synchronously, the phase transition is carried out at a lower temperature, the undercooling degree is greater, the atomic diffusion ability is weakened, the carbide nucleation rate is increased, and the growth rate is slowed down, so that finer sorbite lamellas are formed. Even if the specification of the wire rod is increased, the core can also avoid forming coarse pearlite due to low cooling speed, and the finer the lamellas, the higher the strength of the wire rod. In this way, the basic strength is provided, and the strength loss caused by the appropriate reduction of C or alloy content is compensated. At the same time, the constant temperature characteristic of the molten salt can stabilize the temperature of the wire rod in the sorbite phase transition interval, so that even if the specification of the wire rod is reduced, the formation of martensite and other low-temperature brittle structures due to local composition segregation and local undercooling can be avoided, and the uniformity of the organization and the plasticity can be affected.

[0014] Secondly, compared with controlling the material cost, the structure stress is large in Stelmor air cooling phase change process, it is difficult to consider the high plasticity and rapid and stable production. On the one hand, the wire rod can form the structure with fine interlamellar spacing by the front stage molten salt treatment, the strength stability is improved by uniform strengthening, the internal stress caused by the structure difference is reduced, and the softening difficulty is appropriately reduced. The wire rod can promote the wire rod to be consistent with the molten salt temperature by the rear stage molten salt treatment, the partial sorbite cementite lamella after phase change is promoted to melt and break rapidly to spheroidization by isothermal treatment instead of continuous cooling, the structure stress is further released, and the plasticity and high strength matching of the wire rod are improved. On the other hand, the molten salt temperature of the rear stage molten salt treatment is appropriately reduced compared with the front stage molten salt treatment, and the structure is fully changed and the strength loss is reduced by combining with rapid treatment and avoiding excessive softening of the structure. The wire rod is slowly cooled on the roller after the wire rod is discharged from the molten salt. The higher temperature coiling does not continue to form abnormal brittle structure due to the austenite residue, promotes stable production, and can promote the structure of the wire rod to be further toughened and improve the tempering softening effect by using the high temperature state of the wire rod after being discharged from the molten salt, and does not need to adopt continuous cooling treatment for a long time to affect the production efficiency. Therefore, the strength and plasticity matching of the wire rod is improved, and the stable wire steel base material performance is provided under the conditions of controlling the material cost and production efficiency.

[0015] Before the rolling, the appropriate heating furnace soaking temperature and soaking time in the furnace can improve the austenite uniformity and rolling plasticity, promote the composition homogenization, reduce the composition segregation in the billet, and avoid the austenite grain coarsening and decarburization caused by the too high temperature and too long time in the furnace. In the preferred technical scheme, before the rolling, the heating furnace soaking temperature is controlled to be 1150-1200℃, and the soaking time in the furnace is controlled to be 200-280min.

[0016] During the rolling, the appropriate initial rolling temperature can reduce the cracks and rolling line wear defects caused by the too low initial rolling temperature and insufficient rolling plasticity of the rolled piece, and avoid the grain coarsening in the rolling process caused by the too high initial rolling temperature. The appropriate final rolling temperature and final rolling reduction can accumulate sufficient deformation energy, promote the dynamic recrystallization in the final rolling process, refine the grains, and avoid the excessive residual stress caused by the too low final rolling temperature and too large final rolling reduction. In the preferred technical scheme, during the rolling, the initial rolling temperature is controlled to be 1040-1070℃, the final rolling temperature is controlled to be 910-940℃, and the final rolling reduction is controlled to be 25%-30%.

[0017] During the wire drawing, the wire drawing temperature can be further controlled to reduce the risk of austenite grain coarsening. In the preferred technical scheme, during the wire drawing, the wire drawing temperature is controlled to be 885-920℃.

[0018] The molten salt temperature of the front-stage molten salt treatment is in the sorbite phase region, and the lower the molten salt temperature is, the more conducive to improving the supercooling degree, promoting the rapid cooling of the wire rod, inhibiting the formation of network carbide, reducing the carbon atom diffusion speed, promoting the nucleation and refinement of the sorbite lamella, promoting the full transformation of austenite to sorbite and improving the uniformity of the whole cross-section structure with the extension of the treatment time, but the lower molten salt temperature will increase the internal stress accumulation, even the austenite will cross the sorbite phase region to form hard and brittle structures such as bainite and martensite, increase the brittleness of the wire rod, and the extension of the treatment time will increase the production energy consumption, and the higher molten salt temperature of the front-stage molten salt treatment will accelerate the softening of the wire rod and cause a certain strength loss; on the contrary, the higher the molten salt temperature is, the lower the temperature difference from the surface to the core of the wire rod and the stress accumulation will be, the risk of precipitation of brittle abnormal structure will be reduced, so as to soften the subsequent structure, the shorter the treatment time will be, the production energy consumption will be reduced and a small amount of residual austenite will be retained in the structure; but the higher molten salt temperature is not conducive to inhibiting the network carbide and the grain boundary embrittlement, and the atom diffusion speed is accelerated, so that the lamellar structure is more prone to coarsening, the strength performance is lost, and the shorter the treatment time is, the carbon atom diffusion is insufficient, the risk of coarsening of the core structure will be increased, and the mechanical properties will be fluctuated and the strength will be decreased, therefore, the molten salt temperature and the treatment time of the front-stage molten salt treatment can be controlled to control the wire rod to quickly pass through the network carbide formation region into the sorbite phase region from the high-temperature austenite state, inhibit the formation of network carbide and form a structure mainly of fine lamellar spacing sorbite structure, and prepare for the rear-stage molten salt treatment in terms of structure, and in the preferred technical solution, the molten salt temperature of the front-stage molten salt treatment is 490-540℃, and the treatment time is 35-75s.

[0019] The temperature difference between the spinning temperature and the molten salt temperature of the front-stage molten salt treatment is large, the larger molten salt circulation amount of the front-stage molten salt treatment can control the molten salt temperature rise, promote the rapid cooling of the wire rod, reduce the temperature difference of each part of the wire rod, and further reduce the risk of fluctuation of the structure difference and the mechanical properties, and in the preferred technical solution, the molten salt circulation amount of the front-stage molten salt treatment is 500-650t / h, and the molten salt temperature rise is ≤8℃.

[0020] The molten salt temperature of the latter stage molten salt treatment is appropriately reduced compared to the former stage molten salt treatment. The higher the molten salt temperature and the longer the treatment time, the greater the atomic diffusion capacity, which can provide more thermal power to promote the melting of cementite lamella of sorbite and the transformation to spheroidization, thereby releasing the organizational stress, improving the plasticity and toughness of the wire rod, and promoting the melting of sorbite to disperse and strengthen the matrix and improve the uniformity of the structure, but the high molten salt temperature is not conducive to the control of the transformation of the untransformed residual austenite to the refined sorbite structure, and the increase of the atomic diffusion capacity will drive the melting structure to grow along the grain boundary to form coarse carbide with the extension of the treatment time, which will excessively soften and reduce the strength, and the coarse carbide will become a stress concentration point and reduce the plasticity. On the contrary, the lower the molten salt temperature, the more conducive to the transformation of residual austenite to sorbite, the lower the proportion of ferrite and the atomic diffusion speed, and the shorter the treatment time, which can reduce the production energy consumption and avoid the loss of strength due to excessive softening. However, the low molten salt temperature and short treatment time will affect the melting of cementite lamella, the organizational residual stress will affect the plasticity of the wire rod and increase the risk of deformation and cracking during drawing, and even abnormal structure will be formed in the subsequent cooling process due to the residual austenite. Therefore, the molten salt temperature and treatment time of the latter stage molten salt treatment can be controlled to promote the transformation of untransformed residual austenite to fine lamellar sorbite structure, and the fine lamellar sorbite structure formed is subjected to long-time isothermal tempering to promote the melting of part of the cementite lamella to spheroidization, and the strength and plasticity of the wire rod are quickly processed and matched. In the preferred technical solution, the molten salt temperature of the latter stage molten salt treatment is 400-445℃, and the treatment time is 35-95s.

[0021] The temperature difference of the molten salt of the former stage molten salt treatment and the latter stage molten salt treatment is small, and the molten salt circulation amount of the latter stage molten salt treatment is appropriately reduced to control the molten salt temperature rise, improve the uniformity of the structure and reduce the production energy consumption. In the preferred technical solution, the molten salt circulation amount of the latter stage molten salt treatment is 240-350t / h, and the molten salt temperature rise is ≤3℃.

[0022] The roller slow cooling can further control the slow cooling speed to further toughen the structure of the wire rod and improve the tempering softening effect of the wire rod. In the preferred technical solution, the roller slow cooling controls the wire rod to be cooled to below 280℃ at a slow cooling speed of ≤0.5℃ / s for coiling, and the slow cooling speed can be further preferably 0.3-0.5℃ / s to improve the production efficiency of the wire rod.

[0023] In the preferred technical solution, the roller slow cooling adopts the control of the opening degree of the heat preservation cover, blows the ≥250℃ hot air of the online molten salt isothermal treatment to the conveying roller, and the wire rod is conveyed through the heat preservation cover by the conveying roller, which can recover the heat energy in the production process, reduce the production energy consumption and improve the wire rod offline speed.

[0024] A hot-rolled wire rod for 1960MPa grade stranded wire is manufactured by the method for manufacturing a hot-rolled wire rod for 1960MPa grade stranded wire.

[0025] The hot-rolled wire rod has a high-carbon chemical composition design of Cr-B, relatively low carbon or alloy content, relatively simple composition design, and trace addition of B, so that the material cost can be appropriately controlled. Compared with the existing air-cooled wire rod for stranded wire steel, the microstructure of the hot-rolled wire rod mainly includes mixed structures of tempered sorbite and melted sorbite with a small amount of ferrite, which can eliminate hard and brittle structures such as network carbide and martensite, avoid the splitting effect of network carbide and abnormal hard and brittle structures, and the resulting plasticity loss and strength fluctuation. Through the transformation of austenite structure to sorbite structure with finer interlamellar spacing, the coarse pearlite and the proportion of ferrite are reduced, the strength loss and performance fluctuation caused by structural differences are reduced, the strengthening effect of carbon elements is improved, and through the refinement of the structure and uniform strengthening, higher initial strength of the wire rod can be achieved at a lower alloy content. At the same time, through the melting of the cementite lamella of part of the sorbite, the transition state of the tempered sorbite to spheroidized structure is transformed into melted sorbite and tempered sorbite, which can further reduce stress concentration, improve the plasticity of the matrix, maintain the strength characteristics, improve the matching of high strength and plasticity of the hot-rolled wire rod, avoid the dependence on large reduction ratio drawing due to the insufficient initial strength of the hot-rolled wire rod, and further reduce the plasticity loss in the drawing process. The improvement of plasticity and uniformity of the structure also makes the deformation coordination better during the drawing process, the stress deformation of each region is synchronized, the plasticity loss is more gentle, the generation of grain boundary crack sources is reduced, the risk of wire breakage is reduced, and the safety and service performance of high-strength steel stranded wire are improved.

[0026] In the microstructure, the higher the volume percentage of the tempered sorbite and the finer the interlamellar spacing, the finer and more uniform the structure, which can hinder dislocation movement, improve the matrix strength, and reduce the initiation of fatigue crack sources. In the preferred technical solution, the volume percentage of the tempered sorbite is ≥82%, the interlamellar spacing is 75-120nm, and the volume percentage of the ferrite is ≤8%.

[0027] The reduction of the network carbide level and the improvement of the uniformity of the structure of the hot-rolled wire rod can reduce the tensile strength fluctuation of the wire rod. In the preferred technical solution, the network carbide level of the hot-rolled wire rod is 0 level, and the mechanical property difference between the same circle is ≤32MPa, which can improve the consistency of the processing performance of the wire rod and the product qualification rate, avoid the wire breakage caused by local over-hardening, make the stress more uniform during the service of the stranded wire, and avoid the risk of overall failure caused by local insufficient strength.

[0028] In the preferred technical scheme, the diameter of the hot-rolled wire rod is 8.0-16.0 mm, the tensile strength is 1305-1355 MPa, and the reduction of area is 37%-42%. The higher the tensile strength of the wire rod, the lower the drawing pass and the plastic loss in the drawing process, and the faster the target strength is reached. The wire rod has high plasticity, which is manifested by high reduction of area, and can reduce the risk of wire breakage in the drawing process and avoid brittle fracture of the strand during twisting.

[0029] Compared with the prior art, the present application has at least the following beneficial effects: (1) In view of the fact that it is difficult to control the network carbide, abnormal structure, uniformity of structure and plasticity of the Stelmor air cooling line in the production process of the high-carbon steel hot-rolled wire rod of the steel strand, and the strengthening effect is weakened, the present application combines the high-carbon chemical composition design of Cr-B with the rapid online molten salt isothermal technology. The wire rod after wire feeding is controlled to pass through the network carbon interval from the high-temperature austenite state to the sorbite phase zone, inhibit the formation of network carbon, and form a structure mainly composed of fine lamellar interlaminar sorbite structure. Then, the wire rod is subjected to the second molten salt treatment, the untransformed residual austenite is further transformed into fine lamellar interlaminar sorbite structure, the formed fine lamellar interlaminar sorbite structure is isothermal tempered for a long time, and the cementite sheets of part of the sorbite are melted off, so as to control the strength and plasticity matching of the wire rod. Finally, the slow cooling on the roller promotes the further toughening of the structure of the wire rod and improves the tempering softening effect of the wire rod. The present application can control the material cost and the uniformity of the structure, reduce the risk of network carbide and abnormal structure, improve the matching of the high strength and plasticity of the wire rod, and has good industrial adaptability.

[0030] (2) In view of the fact that the increase of the strength grade of the steel strand leads to high alloy cost of the hot-rolled wire rod, high risk of abnormal structure such as network carbide and martensite, and high risk of wire breakage in the drawing process, the present application appropriately reduces the content of C or alloy compared with the existing wire rod of the strand steel, does not contain V and other elements, and adds B in a small amount. The present application can appropriately control the material cost, the microstructure includes a mixed structure composed of tempered sorbite, ferrite and melted sorbite, can inhibit the precipitation of abnormal structures such as network carbide and martensite, can maximize the strengthening effect of carbon elements and provide basic strength through uniform fine lamellar sorbite, can further release stress and control the plasticity of the structure through tempering state regulation, can improve the overall strength and plasticity of the wire rod, and can be used as a mother material to manufacture 1960 MPa grade strand and other application fields. The present application can reduce the risk of wire breakage in the drawing and twisting processes, meet the development of light weight, meet the demand for higher bearing stress and longer service life, and has good market application prospect. BRIEF DESCRIPTION OF DRAWINGS

[0031] The above and / or additional aspects and advantages of the present application will become apparent and be readily appreciated from the description of the embodiments, taken in conjunction with the following drawings in which: Figure 1 is a metallographic structure diagram of the present application embodiment 1; Figure 2 is a metallographic structure diagram of the present application embodiment 2; Figure 3 is a metallographic structure diagram of the present application embodiment 3. DETAILED DESCRIPTION

[0032] The embodiments described below by reference to the drawings are exemplary only and are merely intended to illustrate the description of the features and characteristics of the present application, to propose the best mode of carrying out the present application, and are intended to serve for the explanation of the present application and are sufficient to enable a person skilled in the art to carry out the present application, and cannot be understood as any limitation on the scope of the present application, the scope of the present application is limited only by the appended claims; the organization and performance detection of the hot-rolled wire rod obtained by the following examples and comparative examples include: tensile test is tested according to GB-T228.1-2021 metal material tensile test part 1: room temperature test method to obtain tensile strength and reduction of area; the organization detection is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: 2 circles of wire rod are taken 5m away from the end of the coil, the lap joint area position is taken as the base point, each circle of wire rod is equally divided into 8 segments, and 1 tensile sample is taken on each segment, and the strength range of the tensile sample after tensile test is the mechanical property same circle difference. Example 1:

[0033] In a preferred embodiment of the manufacturing method of the hot-rolled wire rod for 1960MPa grade twisted wire, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.79%, Si: 0.33%, Mn: 0.63%, Cr: 0.40%, B: 0.005%, P: 0.014%, S: 0.014%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling→ wire drawing→ rapid online molten salt isothermal→ roller slow cooling→ coil collecting, specifically: The rolling process is used for heating the steel billet with a specification of 220mm*220mm to a high-temperature steel billet with a rolling plasticity through a heating furnace, controlling the heating furnace parameters to promote the uniform diffusion of alloy components and avoid decarburization, and rolling the steel billet into a wire rod with a diameter specification of 16mm through a rolling line after the steel billet is out of the heating furnace, selecting appropriate rolling temperature and reduction to promote rapid rolling deformation of the steel billet, and controlling the dynamic recrystallization grain refinement in the finishing rolling process, specifically: controlling the soaking temperature of the heating furnace to be 1170℃, the furnace time to be 250min, the rough rolling temperature to be 1055℃, the finishing rolling temperature to be 920℃, and the finishing rolling reduction to be 25%; the wire-rod laying process is used for laying the wire rod out of the rolling line into a coil through a wire-rod laying machine, and the coil is scattered on a roller way and conveyed along the roller way, and appropriate wire-rod laying temperature is selected to make the coil in a high-temperature austenite state to avoid the precipitation of net-shaped carbide at the wire-rod laying stage and provide favorable conditions for the rapid nucleation of sorbite later, specifically: controlling the wire-rod laying temperature to be 895℃.

[0034] The rapid online molten salt isothermal process adopts two-stage salt bath tanks with molten salt, the coil after wire-rod laying is conveyed through the first-stage salt bath tank for front-stage molten salt treatment, the coil is cooled at a cooling rate of 38℃ / s, quickly passes through the net-shaped carbide interval from the high-temperature austenite state into the sorbite phase interval, inhibits the formation of net-shaped carbide, forms the organization mainly with fine lamellar interlaced sorbite organization, is conveyed through the second-stage salt bath tank for rear-stage molten salt treatment, reduces the molten salt temperature and the molten salt circulation amount, promotes the unconverted residual austenite to continue to be converted into fine lamellar interlaced sorbite organization, at the same time, promotes the formed fine lamellar interlaced sorbite organization to be isothermal tempered for a long time, and melts part of the cementite sheet to adjust and control the strength and plasticity matching of the coil, specifically: the molten salt temperature of the front-stage molten salt treatment is 490℃, the treatment time is 75s, the molten salt circulation amount is 650t / h, and the molten salt temperature rise is ≤8℃; the molten salt temperature of the rear-stage molten salt treatment is 400℃, the treatment time is 35s, the molten salt circulation amount is 350t / h, and the molten salt temperature rise is ≤3℃.

[0035] The roller slow cooling process adopts a control over the opening degree of the heat preservation cover, blows the hot air with a temperature ≥250℃ above the two-stage salt bath tanks of the rapid online molten salt isothermal treatment to the conveying roller way, and conveys the coil through the heat preservation cover through the conveying roller way to promote the further toughening of the coil organization and improve the tempering softening effect of the coil, specifically: the coil is cooled to 275℃ at a slow cooling rate of 0.3℃ / s; the coiling process is used for coiling the coil into a coil through a coiling drum, and the hot-rolled coil product is obtained after packaging and warehousing, and the metallographic organization diagram is as follows Figure 1The microstructure includes 89% of tempered sorbite, 5% of ferrite and 6% of melting sorbite by volume percentage, the lamellar spacing of the tempered sorbite is 76 nm, the reticular carbide level is 0 level, the mechanical property difference of the same circle is 32 MPa, the tensile strength is 1350 MPa, and the reduction of area is 37%.

[0036] Comparative Example 1 A manufacturing method of hot-rolled wire rod, which is different from the manufacturing method of Example 1 in that the manufacturing method is manufactured according to the process flow of rolling → wire drawing → Stelmor strong air cooling, specifically: the soaking temperature of the heating furnace is controlled to be 1140℃, the furnace time is 200min, the rough rolling temperature is 1030℃, the finish rolling temperature is 900℃, and the wire drawing temperature is 880℃; the Stelmor strong air cooling adopts the air volume of each fan to be 260,000m 3 / h, 1~5# fans are opened at 75%, the wire rod is cooled to 670℃ at a cooling rate of 7.2℃ / s, then 6~14# fans are opened at 35%, the wire rod is cooled to 270℃ at a cooling rate of 3.8℃ / s, and the hot-rolled wire rod product is obtained after offline, the microstructure includes 36% of sorbite, 48% of pearlite and 16% of ferrite by volume percentage, the lamellar spacing of the sorbite is 142nm, the lamellar spacing of the pearlite is 225nm, the reticular carbide level is 2 level, the mechanical property difference of the same circle is 87MPa, the tensile strength is 1130MPa, and the reduction of area is 29%.

[0037] From the comparison results of Example 1 and Comparative Example 1, compared with reducing the contents of carbon and alloy elements, it is difficult to control the reticular carbide, abnormal organization, organization uniformity and plasticity, the slow cooling of the core will lead to the coarsening of the pearlite lamella, weaken the strengthening effect, and bring larger mechanical property fluctuation, while the present application can inhibit the formation of reticular carbide and form the organization mainly with fine lamellar spacing sorbite organization, inhibit the coarse pearlite organization, reduce the ferrite proportion, effectively improve the strengthening effect of carbon element, avoid the formation of martensite and other low-temperature brittle abnormal organizations, promote the melting of part of the cementite lamella of the sorbite and the spheroidization transformation, control the organization uniformity, reduce the mechanical property fluctuation, and improve the high strength and plasticity matching of the wire rod.

[0038] Comparative Example 2 A manufacturing method of hot-rolled wire rod, the manufacturing method is different from that of example 1 in that: the soaking temperature of the heating furnace is controlled to be 1080 DEG C, the furnace time is 300 min, the rough rolling temperature is 990 DEG C, the finish rolling temperature is 870 DEG C, the wire rod is cooled at a cooling rate of 31 DEG C / s before the pre-stage molten salt treatment of the rapid online molten salt isothermal process, and the hot-rolled wire rod product is obtained after being discharged. Example 2:

[0039] In a preferred embodiment of the manufacturing method of the 1960 MPa grade hot-rolled wire rod for stranded wire, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.79%, Si: 0.35%, Mn: 0.55%, Cr: 0.36%, B: 0.001%, P: 0.015%, S: 0.015%, and the rest is Fe and inevitable impurities; the manufacturing method is manufactured according to the process flow of rolling → wire drawing → rapid online molten salt isothermal → slow cooling on roller → coiling, specifically: The rolling process is used to heat the steel billet with a size of 180 mm*180 mm to a high-temperature steel billet with a rolling plasticity by a heating furnace, control the heating furnace parameters to promote the uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire rod with a diameter size of 8 mm after the steel billet is discharged from the heating furnace through a rolling line, select appropriate rolling temperature and reduction, promote rapid rolling deformation of the steel billet, control the dynamic recrystallization of the finish rolling process to refine the grains, specifically: control the soaking temperature of the heating furnace to be 1150 DEG C, the furnace time is 280 min, the rough rolling temperature is 1040 DEG C, the finish rolling temperature is 910 DEG C, and the finish rolling reduction is 30%; the wire drawing process is used to make the wire rod discharged from the rolling line into a wire rod through a wire drawing machine, the wire rod is scattered on the roller and conveyed along the roller, the appropriate wire drawing temperature is selected to make the wire rod in the high-temperature austenite state, avoid the precipitation of net-shaped carbide at the wire drawing stage, and provide favorable conditions for the subsequent sorbite rapid nucleation, specifically: control the wire drawing temperature to be 885 DEG C.

[0040] The rapid online molten salt isothermal process adopts two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the first-stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 32℃ / s, quickly passes through the interlaced carbide interval from the high-temperature austenite state into the sorbite phase interval, inhibits the formation of interlaced carbide, forms a structure mainly of fine lamellar interlaced sorbite structure, and then is conveyed through the second-stage salt bath tank for rear-stage molten salt treatment, reduces the molten salt temperature and the molten salt circulation amount, promotes the unconverted residual austenite to continue to be converted into fine lamellar interlaced sorbite structure, at the same time promotes the formed fine lamellar interlaced sorbite structure to be tempered for a long time, and causes part of the cementite sheets to be broken, so as to regulate and control the strength and plasticity matching of the wire rod. Specifically, the molten salt temperature of the front-stage molten salt treatment is 540℃, the treatment time is 35s, the molten salt circulation amount is 500t / h, and the molten salt temperature rise is ≤8℃; the molten salt temperature of the rear-stage molten salt treatment is 445℃, the treatment time is 95s, the molten salt circulation amount is 240t / h, and the molten salt temperature rise is ≤3℃.

[0041] The roller slow cooling process blows hot air ≥250℃ above the two-stage salt bath tank of the rapid online molten salt isothermal treatment to the conveying roller through controlling the opening degree of the heat preservation cover, so that the wire rod is conveyed through the heat preservation cover by the conveying roller, promotes the further toughening of the wire rod structure, and improves the tempering softening effect of the wire rod. Specifically, the wire rod is cooled to 271℃ at a slow cooling rate of 0.5℃ / s. Figure 2

[0042] Comparative Example 3 A manufacturing method of hot-rolled wire rod, which is different from that of Example 2 in that, in the front-stage molten salt treatment of the rapid online molten salt isothermal process, the wire rod is cooled at a cooling rate of 37℃ / s, the molten salt temperature of the front-stage molten salt treatment is 485℃, and the treatment time is 90s. The hot-rolled wire rod product is obtained after being discharged.

[0043] Comparative Example 4 A manufacturing method of hot-rolled wire rod, which is different from that of Example 2 in that, in the front-stage molten salt treatment of the rapid online molten salt isothermal process, the wire rod is cooled at a cooling rate of 30℃ / s, the molten salt temperature of the front-stage molten salt treatment is 565℃, and the treatment time is 30s. The hot-rolled wire rod product is obtained after being discharged. Example 3

[0044] ​The chemical composition and mass percentage of the hot rolled wire rod for 1960MPa grade stranded wire according to a preferred embodiment of the manufacturing method of the present application include C: 0.81%, Si: 0.40%, Mn: 0.65%, Cr: 0.25%, B: 0.005%, P: 0.012%, S: 0.014%, and the rest is Fe and inevitable impurities; and the manufacturing method is manufactured according to the process flow of rolling→ wire drawing→ fast online molten salt isothermal→ slow cooling on roller table→ coiling, and specifically: The rolling process is used to heat the steel billet with a specification of 220mm*220mm to a high-temperature steel billet with rolling plasticity through a heating furnace, control the heating furnace parameters to promote the uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire rod with a diameter specification of 11mm through a rolling line after the steel billet is out of the heating furnace, select appropriate rolling temperature and reduction, promote rapid rolling deformation of the steel billet, control the dynamic recrystallization grain refinement in the final rolling process, and specifically: the soaking temperature of the heating furnace is controlled to be 1190℃, the in-furnace time is 235min, the initial rolling temperature is 1065℃, the final rolling temperature is 930℃, and the final rolling reduction is 28.5%; the wire drawing process is used to draw the wire rod out of the rolling line through a wire drawing machine to form a wire rod, the wire rod is scattered on a roller table and conveyed along the roller table, and appropriate wire drawing temperature is selected to make the wire rod in a high-temperature austenite state to avoid the precipitation of net-shaped carbide at the wire drawing stage and provide favorable conditions for the rapid nucleation of sorbite later, and specifically: the wire drawing temperature is controlled to be 910℃.

[0045] The fast online molten salt isothermal process adopts two-stage salt bath tanks with molten salt, the wire rod after wire drawing is conveyed through the first-stage salt bath tank for front-stage molten salt treatment to make the wire rod cool down at a cooling rate of 37℃ / s, quickly pass through the net-shaped carbide interval from the high-temperature austenite state into the sorbite phase interval, inhibit the formation of net-shaped carbide, form a structure mainly of fine lamellar interlaced sorbite structure, and then be conveyed through the second-stage salt bath tank for rear-stage molten salt treatment, reduce the molten salt temperature and molten salt circulation amount, promote the residual untransformed austenite to continue to transform into fine lamellar interlaced sorbite structure, at the same time, promote the formed fine lamellar interlaced sorbite structure to be isothermal tempered for a long time, and make part of cementite sheets melt, so as to adjust and control the strength and plasticity matching of the wire rod, and specifically: the molten salt temperature of the front-stage molten salt treatment is 509℃, the treatment time is 42s, the molten salt circulation amount is 575t / h, and the molten salt temperature rise is ≤8℃; the molten salt temperature of the rear-stage molten salt treatment is 425℃, the treatment time is 80s, the molten salt circulation amount is 285t / h, and the molten salt temperature rise is ≤3℃.

[0046] The roller slow cooling process adopts control of the opening of the heat preservation cover, and hot air with a temperature of ≥250℃ above the two-stage salt bath tank for isothermal treatment of the fast online molten salt is blown to the conveying roller, and the wire rod is conveyed through the heat preservation cover by the conveying roller, so as to promote further toughening of the wire rod structure and improve the wire rod tempering softening effect. Specifically, the wire rod is cooled to 273℃ at a slow cooling speed of 0.4℃ / s; the coiling process is used to coil the wire rod into a coil through the coiling drum, and the hot rolled wire rod product is obtained after packaging and storage, and the metallographic structure diagram is as shown in Figure 3 .

[0047] Comparative Example 5 A manufacturing method of a hot rolled wire rod, which is different from that of Example 3 in that the molten salt temperature of the second-stage molten salt treatment is 465℃, and the treatment time is 130s, and the hot rolled wire rod product is obtained after offline.

[0048] Comparative Example 6 A manufacturing method of a hot rolled wire rod, which is different from that of Example 3 in that the molten salt temperature of the second-stage molten salt treatment is 395℃, and the treatment time is 30s, and the hot rolled wire rod product is obtained after offline. Example 4

[0049] In a preferred embodiment of the manufacturing method of the 1960MPa-grade hot rolled wire rod for stranded wire, the chemical composition and mass percentage of the hot rolled wire rod include C: 0.83%, Si: 0.20%, Mn: 0.59%, Cr: 0.20%, B: 0.008%, P: 0.014%, S: 0.015%, and the rest is Fe and inevitable impurities; the manufacturing method is manufactured according to the process flow of rolling→ wire laying→ fast online molten salt isothermal treatment→ roller slow cooling→ coiling, and specifically: The rolling process is used to heat the steel billet with a specification of 220mm×220mm to a high-temperature steel billet with a rolling plasticity by a heating furnace, control the heating furnace parameters to promote the uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire rod with a diameter specification of 14mm by a rolling line after the steel billet is out of the heating furnace, select appropriate rolling temperature and reduction, promote rapid rolling deformation of the steel billet, control the dynamic recrystallization grain refinement in the final rolling process, and specifically: control the soaking temperature of the heating furnace to be 1200℃, the time in the furnace is 200min, the initial rolling temperature is 1070℃, the final rolling temperature is 940℃, and the final rolling reduction is 26%; the wire laying process is used to lay the wire rod out of the rolling line into a wire rod through a wire laying machine, and the wire rod is scattered on the roller and conveyed along the roller, and appropriate wire laying temperature is selected to make the wire rod in a high-temperature austenite state, avoid the precipitation of network carbide at the wire laying stage, and provide favorable conditions for the subsequent spheroidizing rapid nucleation, and specifically: control the wire laying temperature to be 920℃.

[0050] The rapid online molten salt isothermal process adopts two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the first-stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 37 ℃ / s from high-temperature austenite state to quickly pass through the intercritical region of the network carbide and enter the sorbite phase region, inhibit the formation of network carbide, and form a structure mainly of fine lamellar interlaminar sorbite structure. The wire rod is then conveyed through the second-stage salt bath tank for rear-stage molten salt treatment, the molten salt temperature and molten salt circulation amount are reduced, the untransformed residual austenite is promoted to continue to transform into fine lamellar interlaminar sorbite structure, the formed fine lamellar interlaminar sorbite structure is promoted to isothermal tempering for a long time, and part of the cementite sheet is broken to adjust and control the strength and plasticity matching of the wire rod. Specifically, the molten salt temperature of the front-stage molten salt treatment is 522 ℃, the treatment time is 60 s, the molten salt circulation amount is 620 t / h, and the molten salt temperature rise is ≤8 ℃; the molten salt temperature of the rear-stage molten salt treatment is 410 ℃, the treatment time is 65 s, the molten salt circulation amount is 310 t / h, and the molten salt temperature rise is ≤3 ℃.

[0051] The roller slow cooling process blows hot air ≥250 ℃ above the two-stage salt bath tank of the rapid online molten salt isothermal treatment to the conveying roller through controlling the opening degree of the heat preservation cover, and the wire rod is conveyed through the heat preservation cover by the conveying roller to promote the further toughening of the wire rod structure and improve the tempering softening effect of the wire rod. Specifically, the wire rod is cooled to 276 ℃ at a slow cooling rate of 0.45 ℃ / s; and the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.

[0052] Comparative Example 7 A manufacturing method of a hot-rolled wire rod, which is different from the manufacturing method of Example 4 in that the manufacturing method is manufactured according to the process flow of rolling→spinning→rapid online molten salt isothermal treatment→air cooling, the air cooling process adopts opening the heat preservation cover and controlling the wire rod to be cooled to 265 ℃ at a slow cooling rate of 1.1 ℃ / s, and the hot-rolled wire rod product is obtained after offline.

[0053] The wire rod products obtained in Examples 1-4 and Comparative Examples 2-7 are subjected to structure and performance detection, and the comparison results are shown in Table 1 as follows: Table 1. Comparison results of structure and performance of different hot-rolled wire rod compositions and manufacturing methods

[0054] As can be seen from the comparison results of Example 1 and Comparative Example 2, a higher spinning temperature is adopted to ensure that the wire rod is in a high-temperature austenitizing state, which can prevent the network carbide from precipitating too early, provide favorable conditions for improving the undercooling degree, promoting the rapid nucleation of sorbite structure and refining the lamellar structure, and at the same time, can reduce the limitation on the rolling temperature to improve the rolling efficiency.

[0055] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the molten salt temperature of the front-stage molten salt treatment is in the sorbite phase region, the lower the molten salt temperature, the more conducive to improving the undercooling degree, promoting the rapid cooling of the rod, inhibiting the formation of network carbide, and reducing the carbon atom diffusion speed, promoting the nucleation and refinement of sorbite lamella, and with the extension of the treatment time, it is conducive to promoting the full transformation of austenite to sorbite and improving the uniformity of the whole cross-section structure, but if the molten salt temperature is too low, it will increase the internal stress accumulation and the brittleness of the rod, and with the extension of the treatment time, it will increase the production energy consumption, and if the treatment time is too long, the molten salt temperature of the front-stage molten salt treatment will be higher, which will accelerate the softening of the rod and cause a certain strength loss.

[0056] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front-stage molten salt treatment, the lower the temperature difference from the surface to the core of the rod and the stress accumulation, and the lower the risk of brittle abnormal structure precipitation, so as to soften the subsequent structure, and with the reduction of the treatment time, the production energy consumption can be reduced and a small amount of residual austenite can be retained in the structure; but if the molten salt temperature is too high, it is not conducive to inhibiting the network carbide and the brittle of the grain boundary, and at the same time, the atomic diffusion speed is accelerated, so that the lamellar structure is more prone to coarsening, resulting in a loss of strength performance, and with the shortening of the treatment time, the carbon atom diffusion is not sufficient, which will increase the risk of coarsening of the core structure and cause fluctuations in mechanical properties and a decrease in strength.

[0057] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the molten salt temperature of the rear-stage molten salt treatment is appropriately lower than that of the front-stage molten salt treatment, the higher the molten salt temperature and the longer the treatment time, the greater the atomic diffusion ability, which can provide more thermal power to promote the melting of the cementite lamella of sorbite and the transformation to spheroidization, which not only releases the structure stress, improves the plasticity and toughness of the rod, but also strengthens the matrix through the dispersion of the melted sorbite, and improves the uniformity of the structure, but if the molten salt temperature is too high, it is not conducive to the control of the residual austenite that has not been transformed to continue to transform into refined sorbite structure, and at the same time, the atomic diffusion ability is increased, which will drive the melted structure to grow along the grain boundary and form coarse carbide with the extension of the treatment time, which will excessively soften and reduce the strength, and the coarse carbide will become a stress concentration point and reduce the plasticity.

[0058] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the lower the molten salt temperature of the rear-stage molten salt treatment, the more conducive to promoting the transformation of residual austenite to sorbite, reducing the proportion of ferrite and the atomic diffusion speed, and with the reduction of the treatment time, the production energy consumption can be reduced and the strength loss due to excessive softening can be avoided; but if the molten salt temperature is too low and the treatment time is too short, it will affect the melting of the cementite lamella, and the structure will remain a large stress, which will affect the plasticity of the rod and increase the risk of deformation and cracking during drawing.

[0059] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the slow cooling on the roller can further control the slow cooling speed, promote the further toughening of the rod structure, and improve the tempering softening effect of the rod.

[0060] The above detailed description merely illustrates feasible embodiments of the present application, and is not intended to limit the protection scope of the present application, and equivalent embodiments or changes made without departing from the spirit of the present application shall be included in the protection scope of the present application.

Claims

1. A method for manufacturing a 1960 MPa grade hot-rolled wire rod for stranded wire, characterized in that: The manufacturing method includes: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, and the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.79%~0.83%, Si: 0.20%~0.40%, Mn: 0.55%~0.65%, Cr: 0.20%~0.40%, B: 0.001%~0.008%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into wire rod at a spinning temperature of ≥885°C, and then rapidly The wire rod is subjected to molten salt isothermal treatment. The wire rod first undergoes the front-end molten salt treatment, which makes the wire rod cool down at a cooling rate of ≥32℃ / s, and enters the sorbite phase region from the austenite state, forming a structure dominated by sorbite. The wire rod then undergoes the rear-end molten salt treatment to reduce the molten salt temperature, promote the transformation of untransformed residual austenite to sorbite structure, and at the same time promote isothermal tempering of the structure and melting of part of the sorbite lamellae. Finally, it is slowly cooled by rollers to produce a hot-rolled wire rod with a microstructure consisting of a mixed structure of tempered sorbite, ferrite and fused sorbite.

2. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 1, wherein: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1150-1200° C., and the soaking time in the furnace is 200-280 minutes.

3. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 1, wherein: During the rolling, the initial rolling temperature is controlled to be 1040-1070° C., the final rolling temperature is controlled to be 910-940° C., and the final rolling reduction is controlled to be 25%-30%.

4. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 1, wherein: During the spinning process, the spinning temperature is controlled to be 885-920°C.

5. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 1, wherein: The molten salt temperature of the front-stage molten salt treatment is 490-540° C., and the treatment time is 35-75 seconds; the molten salt temperature of the back-stage molten salt treatment is 400-445° C., and the treatment time is 35-95 seconds.

6. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 5, characterized in that: The molten salt circulation rate of the front-stage molten salt treatment is 500~650t / h, and the molten salt temperature rise is ≤8°C; the molten salt circulation rate of the back-stage molten salt treatment is 240~350t / h, and the molten salt temperature rise is ≤3°C.

7. The method for manufacturing the 1960 MPa grade hot rolled wire rod for stranded wire according to claim 5, characterized in that: The roller slow cooling controls the wire rod to be cooled to below 280° C. at a slow cooling rate of ≤0.5° C. / s for coiling.

8. A 1960MPa grade hot rolled wire rod for stranded wire, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing the hot-rolled wire rod for 1960 MPa grade stranded wire according to any one of claims 1 to 7.

9. The 1960 MPa grade hot rolled wire rod for stranded wire according to claim 8, characterized in that: The volume percentage of the tempered bainite is ≥82%, the interlamellar spacing is 75-120 nm, the volume percentage of the ferrite is ≤8%, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property same-circle difference is ≤32 MPa.

10. The 1960 MPa grade hot rolled wire rod for stranded wire according to claim 8, characterized in that: The hot-rolled wire rod has a diameter of 8.0-16.0 mm, a tensile strength of 1305-1355 MPa, and a cross-sectional shrinkage rate of 37%-42%.

Citation Information

Patent Citations

  • Slow-annealing cold heading steel wire rod for 8.8-grade bolt and manufacturing method of low-annealing cold heading steel wire rod

    CN118086785A

  • B-containing hot-rolled wire rod for 1770MPa-grade stranded wire and manufacturing method of B-containing hot-rolled wire rod

    CN118854175A

  • Hot-rolled carbon wire rod for 1860MPa-grade stranded wire and manufacturing method of hot-rolled carbon wire rod

    CN119040750A

  • Hot-rolled wire rod for 1860MPa bridge cable and manufacturing method of hot-rolled wire rod

    CN119040751A

Cited By

  • Hot-rolled wire rod for 2130MPa-grade stranded wire and manufacturing method of hot-rolled wire rod

    CN121046734A

  • Hot-rolled wire rod for 2260MPa-grade stranded wire and manufacturing method of hot-rolled wire rod

    CN121046739A

  • Hot-rolled wire rod for 2200MPa-grade stranded wire and manufacturing method of hot-rolled wire rod

    CN121046740A